2015
DOI: 10.1016/j.tjem.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of whole-body multislice computed tomography findings taken in trauma patients

Abstract: ObjectivesUsing whole-body multislice computed tomography (MSCT) excessively or with irrelevant indications can be seen in many centers. The aim of this study was to analyze retrospectively the MSCT findings in trauma patients admitted to the emergency department.MethodsRecords of the patients who have applied to the emergency department due to blunt trauma in a 12 month period and whose whole body MSCT images have been taken, were evaluated using the “Nucleus Medical Information System”.ResultsThe most freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…CT is the most rapid and reliable imaging technique for detecting signs of trauma during the management of trauma patients in the emergency department. It was reported that at least one injury existed in 61.4% of CT scans of trauma victims in emergency departments, with the most common injuries being lung contusion and rib fractures 13 . Signs of trauma such as pneumothorax, hemothorax, lung contusion, and solid organ injuries are detected in a majority of patients with severe chest trauma 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…CT is the most rapid and reliable imaging technique for detecting signs of trauma during the management of trauma patients in the emergency department. It was reported that at least one injury existed in 61.4% of CT scans of trauma victims in emergency departments, with the most common injuries being lung contusion and rib fractures 13 . Signs of trauma such as pneumothorax, hemothorax, lung contusion, and solid organ injuries are detected in a majority of patients with severe chest trauma 14,15 .…”
Section: Discussionmentioning
confidence: 99%